Executive Functions and Motivation as Moderators of the Relationship Between Automatic Associations and Alcohol Use in Problem Drinkers Seeking Online Help. (6th August 2015) - van Deursen, Denise S.; Salemink, Elske; Boendermaker, Wouter J.; Pronk, Thomas; Hofmann, Wilhelm; Wiers, Reinout W.
<x xml:space="preserve">Abstract</x> Background Dual process models posit that problem drinking is maintained by an imbalance between relatively strong automatic processes and weak controlled processes, a combination of executive functions and motivation. Few studies have examined how the interplay between automatic processes and executive functions is affected by motivation to change. This study examined this relationship in problem drinkers seeking online help to change their alcohol use. It was expected that executive functions (i.e., working memory, response inhibition) would moderate the relationship between automatic (valence and approach) associations and alcohol use and that this effect would be stronger in individuals with strong motivation to change. Methods A sample of 302 problem drinkers (mean age: 51.7 years) participated in this study as part of the baseline assessment before an Internet intervention. Participants completed an online version of the brief Implicit Association Test (valence and approach associations), the self‐ordered pointing task (working memory), the Stroop task (response inhibition), the Readiness to Change Questionnaire (motivation to change), and the Timeline Follow‐Back Questionnaire (alcohol use). Hierarchical moderated regression analysis was used to test the 4 hypothesized 3‐way interactions. Results As expected, the interaction between valence associations and working memory only predicted alcohol use among individuals with strong motivation. This pattern was neither found for response inhibition nor for approach associations. Conclusions Results provide partial support for the moderating role of motivation in the interplay between automatic processes and executive functions. Future studies should investigate this relationship in participants with the full range of motivation and alcohol use.